Challenges to the performance of the regional health departments in Mauritania: a qualitative study - Mohamed Ali Ag Ahmed; Kirsten Accoe; Karina Kielmann; Bruno Marchal; Verónica Trasancos Buitrago; Hamma Issa Moussa; Bart Criel (BMC Health Services Research)
Abstract Background In sub-Saharan Africa, the regional or intermediary level should play an important role within the health system. It is generally responsible for providing technical support to the health districts, ensuring the contextualisation of policies, and channeling communication between the central and local levels. In this paper, we analyze factors influencing the performance of the two Regional Health Directorates in Mauritania. More specifically, we analyse the main challenges they face and recommend actions to strengthen their performance. Methods A case study approach with a qualitative study design was used. Two Regional Directorate for Health Action (RDHAs) of Brakna and Nouakchott-North were chosen as units of analysis. The study was conducted from February to August 2021 and guided through the conceptual framework of Marchal et al. and triangulation of a document review, focus group discussions and semi-structured individual interviews. A total number of 25 respondents were purposively selected, covering the main stakeholders who manage or collaborate with the RDHAs, until saturation and a certain level of diversification was reached. Thematic content analysis and aided by Nvivo software were used. A mixed (inductive and deductive) approach to analysis was adopted. Results This study assessed the performance of two RDHAs in Mauritania by analysing of their key functions. The participants noted a lack of clarity in their objectives, an overly bureaucratic vision of their functions and inadequate technical capacities hampering the provision of required services. They mentioned weak regional health coordination with stakeholders and a poor organisational culture. These bottlenecks largely limited the capacities of the RDHAs to play their role within the health system in Mauritania. Conclusion This study identified the main gaps in the performance of the Brakna and Nouakchott-North RDHAs. The scale of these challenges does not allow them to engage and mobilise the right stakeholders and appropriate resources to achieve their objectives. We propose to initiate organisational change at the RDHA level. Some actions are discussed.